Principles of Litigation in Labor Lawsuits (A Comparative Study) - Riyad Issa, Researcher.Maryam; Abdul Redha Ali Al-Fardan, Assist .Prof. Dr. Munqith (Basra studies journal, 2024)
Courts specialize in certain types of lawsuits based on their jurisdictional and territorial competence. Given the unique nature of disputes between workers and employers in part-time employment contracts, where there is an inherent imbalance between the two parties—employers typically being the stronger party both materially and socially, while workers are the weaker party—a special judiciary known as labor courts has been established. Labor courts do not rely solely on labor laws to resolve disputes but also apply relevant provisions from civil law, procedural law, and evidence law. Therefore, the jurisdiction of these courts is balanced between criminal and civil jurisdiction. To provide substantial protection to workers, the legislator has structured this judiciary into two levels and established appeal procedures, as well as mechanisms for the statute of limitations in labor lawsuits.